Influence of Altered Immune-Inflammatory Axis on the Risk of Osteomyelitis and Its Network Interaction Effect in European Population - Yangguang Lu; Siyao Chen; Ruotong Yao; Feng Chen; Yukai Wang; Zihui Yuan; Di Lu; Haiyong Ren; Xiang Wang; Bingyuan Lin; Qiaofeng Guo; Kai Huang (Mediators of Inflammation)
Conclusions: This study provides novel insights into the immune–inflammatory axis in OM and identifies potential biomarkers for risk assessment. The findings warrant further validation in diverse populations and pave the way for developing targeted preventive and therapeutic strategies for OM.